The Impact of Visionary Leadership on Science-Based Technology Adoption in East Wawonii Elementary Schools - Abu Bakar; Aspin Aspin; Marwan Marwan; Agus Herwanto; Agung Prihatmojo (STAI Hubbulwathan Duri, 2025)
The integration of technology in science learning has become essential in the era of Industrial Revolution 4.0, particularly in primary education. Visionary leadership by school principals is believed to play a critical role in facilitating the adoption of science-based innovative technology in classrooms. This study employed a quantitative approach using a survey design involving 100 elementary school teachers and principals in East Wawonii who have implemented science-based technology in teaching. Data were collected through a validated Likert-scale questionnaire measuring perceptions of visionary leadership and the extent of technology adoption. Correlation and simple linear regression analyses were conducted using SPSS. The findings revealed a strong and significant relationship between visionary leadership and the adoption of science-based technology (r = 0.87, p = 0.001). Regression analysis confirmed that visionary leadership significantly predicts technology adoption (β = 0.716, p = 0.001), with an R-squared value of 0.757, indicating that 75.7% of the variance in technology adoption can be explained by the leadership variable. These results suggest that visionary leadership is a key driver in promoting technology integration in science learning. Principals who articulate clear long-term goals, inspire innovation, and support teacher development contribute significantly to creating a conducive environment for technology adoption in primary schools. The study highlights the importance of leadership training that focuses on technological awareness and innovation management.